Respuesta :

-3x - y = -17
4x + 2y = 20

multiply one part of the equation so that we can be able to use the process of elimination.

(-3x - y = -17)2
4x + 2y = 20

Now we have:

-6x -2y = - 34
4x+2y= 20
------------------------
-2x = -14

Divide -2 on both sides.

-2x = -14
/-2       /-2

x = -7.


=============================================

To solve for y, we just have to substitute the value of x to any of the equation given above, that we feel comfortable with. And I'm going to choose this equation: 4x + 2y = 20


4x + 2y = 20

4(-7) + 2y = 20

-28 + 2y = 20

Add 28 on both sides

-28 + 2y = 20
+28          +28
---------------------
2y = 48
/2      /2

y = 24.


The last thing you would do is to check if the answers is correct.
All you have to do is plug in the values of x and y into both equations and see if they equal to one another.

You may have to do this by yourself :P

Anyways, if you have any questions about this topic, feel free to PM me or any other users interested. Thank you for being part of Brainly! Have a nice day!